Variable cell division time and asymmetric division site lead to filament-to-rod cell cycle of Lysinibacillus varians. Issue 7 (20th March 2020) - Zhu, Chunjie; Sun, Guoping; Wang, Xiaoming; Guo, Jun; Li, Enze; Yang, Yonggang; Xu, Meiying
ABSTRACT: All well-established cell size homeostasis paradigms are based on the researches of rod bacteria like B. subtilis and E. coli, suggesting a constant division time (timer model), division size (sizer model) or added size (adder model) before division. However, Lysinibacillus varians, a new species with regular filament-to-rod cell cycle, is inconsistent with existing models. In this study, the cell size parameters of the type strain GY32, were investigated by combing multiple microscopy techniques and single-cell approach. Our results showed that the filaments of strain GY32 were unicellular cells with multiple nucleoids. The division time of GY32 cells was variable and their daughter cells produced by asymmetric binary fission had different birth sizes, which were proportional to their elongation rates, resulting in high heterogeneity among the sister cells. Furthermore, the added size from birth to division was significantly shorter than birth size ( p  < 0.01) and decreased along generations. The results above revealed that the asymmetric division site and varied cell size parameters resulted in filament-to-rod cell cycle of L. varians and cell size homeostasis could be a more complex and dynamic process than previously assumed. These findings would be helpful in elucidating the open questions in cell division and cell size heterogeneity. Abstract : Variable division time and asymmetric division site in Lysinibacillus bacteria.